Coordena????o do trabalho pedag??gico na rede estadual paulista: desafios, limites e potencialidades - Silva, Val??ria Andrade (2015)
The main objective of this study on pedagogical coordination in public state schools was the development of a critical reflection on the corresponding daily school practices in order to contribute to broaden the knowledge about this subject matter which has not been much investigated from the perspective of the theoretical and practical challenges historically presented to the coordinating action in public school. The study assumes that pedagogical coordination is an integral part of the set of practices that constitute school management, being defined as the coordination of the collective human effort (PARO, 1986) undertaken in the teaching-learning process, the core of school work. Another assumption of the study is that pedagogical coordination, like every school practice, is a concrete social praxis teleologically oriented. Methodologically, an empirical qualitative study was conduced, combining documental analysis; literature review; observations; and semi-structured interviews with coordinating teacher, principal and teachers of an elementary and high school state public school belonging to the center of S??o Paulo Board of Education. The paper discusses the specific conditions in which the coordinating education practices take place; the redefinition of the responsibilities and expectations of SEE-SP for the teacher coordinator function; the orientation of educational policies in the State of S??o Paulo, focusing on "S??o Paulo faz escola" program and the role of the coordinator teacher in its context; the historical background of the establishment of teaching coordination function in state public schools within the legal standards; and finally it takes a look at this set of data from the theoretical approach that understands the work as an educational principle (Saviani, 1991) and the category labor, in Luk??cs (1981), as an explanatory model of social praxis. There are many limitations and challenges for pedagogical coordination in the state public schools and the discourses about the difficulties and impediments to the achievement of an efficient and effective pedagogical practice by the teacher coordinator appears to be incorporated into the common sense in school, thus, covering the possibility of considering alternatives to transform its reality. Based on the reflection carried out, the study identifies in the coordination of collective human effort the potential of pedagogical coordination to contribute to improve the quality of education and to the universalization of knowledge, ultimate goals of public schools.